1974
DOI: 10.1111/j.1748-1716.1974.tb05562.x
|View full text |Cite
|
Sign up to set email alerts
|

The Distensibility of the Resistance Vessels in Spontaneously Hypertensive Rats (SHR) as Compared with Normotensive Control Rats (NCR)

Abstract: Earlier studies on human essential hypertension, as well as on SHR, suggest that an increased media thickness, partly encroaching upon the vascular lumen, forms the main background of the increased flow resistance in primary hypertension (e.g. Folkow et al. 1970). In the present investigation a comparison was made concerning the distensibility of the resistance vessels in order to further explore the proposed difference in vascular design. The simultaneously perfused hindquarter vessels of SHR and NCR were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1975
1975
1987
1987

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…Several investigators"-" B have found right ventricular hypertrophy in rats with various forms of experimental hypertension, suggesting the presence of elevated right ventricular pressure or flow loads. One group,* 40 however, found that normal right ventricular systolic pressure accompanied right ventricular hypertrophy in pentobarbital anesthetized SHR; this group also reported abnormalities in pulmonary vascular responses to locally administered angiotensin II and prostaglandin F to . Pulmonary artery wall thickness was reported normal unless the rats were subjected to hypoxic stress, at which time arterial hypertrophy was observed in SHR but not in WKY.…”
Section: Hypertensionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several investigators"-" B have found right ventricular hypertrophy in rats with various forms of experimental hypertension, suggesting the presence of elevated right ventricular pressure or flow loads. One group,* 40 however, found that normal right ventricular systolic pressure accompanied right ventricular hypertrophy in pentobarbital anesthetized SHR; this group also reported abnormalities in pulmonary vascular responses to locally administered angiotensin II and prostaglandin F to . Pulmonary artery wall thickness was reported normal unless the rats were subjected to hypoxic stress, at which time arterial hypertrophy was observed in SHR but not in WKY.…”
Section: Hypertensionmentioning
confidence: 99%
“…There is also evidence for reduced arterial distensibility in spontaneously hypertensive rats (SHR). 40 Vascular fibrosis and/or edema may contribute to decreased arterial compliance, but the mechanisms of altered compliance are not fully elucidated.…”
Section: Arterial Compliancementioning
confidence: 99%
See 3 more Smart Citations